2015
DOI: 10.3892/ijmm.2015.2190
|View full text |Cite
|
Sign up to set email alerts
|

CCN5 attenuates profibrotic phenotypes of fibroblasts through the Smad6-CCN2 pathway: Potential role in epidural fibrosis

Abstract: Epidural fibrosis is characterized by the development of dense and thick scar tissue adjacent to the dural mater and ranked as the major contributor for post-operative pain recurrence after laminectomy or discectomy. Recently, CCN5 exhibited an inhibitory effect on connective tissue growth factor (CTGF)/CCN2 (a critical regulator for fibrotic disease)-mediated fibrogenesis. However, its function in epidural fibrosis and the underlying mechanisms involved remain to be determined. In this study, an obvious downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…CTGF has been reported to mediate the TGF-β1-induced upregulation of collagen type I in fibroblasts ( 51 ). An increased CTGF expression in epidural scar tissue plays a key role in EF development by stimulating TGF-β1-induced fibroblast proliferation and ECM production, as well as collagen and fibronectin synthesis ( 13 ). As was expected, it was found that TGF-β1 treatment significantly stimulated the production of CTGF at both the gene and protein levels, which was reversed by honokiol in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…CTGF has been reported to mediate the TGF-β1-induced upregulation of collagen type I in fibroblasts ( 51 ). An increased CTGF expression in epidural scar tissue plays a key role in EF development by stimulating TGF-β1-induced fibroblast proliferation and ECM production, as well as collagen and fibronectin synthesis ( 13 ). As was expected, it was found that TGF-β1 treatment significantly stimulated the production of CTGF at both the gene and protein levels, which was reversed by honokiol in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In epidural fibrosis, CCN5 exerts anti-fibrotic effects by regulating the Smad6-CCN2 pathway. 42 Foxf2 and Smad6 play crucial roles in the production of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that CCN5/WISP2 is anti-fibrotic and counteracts the effects of several fibrotic markers such as CTGF and α-SMA (Xu et al 2015a ; Xu et al 2015b ). In rat scar tissue, where epidural fibrosis was examined, CTGF was upregulated while CCN5/WISP2 was downregulated on both mRNA and protein level.…”
Section: Ccn5/wisp2 and Metabolic Diseasementioning
confidence: 99%
“…Blocking Smad6 phosphorylation ameliorated the inhibitory effect of CCN5/WISP2 on CTGF. When the Smad6 pathway was blocked using siRNA, cell proliferation was once again increased in Ccn5/Wisp2 -overexpressing cells following TGFβ1 stimulation (Xu et al 2015b ). CCN5/WISP2 also normalized the increased Akt phosphorylation induced by TGFβ in cardiac fibroblasts, consistent with the findings seen in fibroblasts of the lung (Jeong et al 2016 ; Zhang et al 2014 ).…”
Section: Ccn5/wisp2 and Metabolic Diseasementioning
confidence: 99%